Mercado minorista sector el Batán - Bohórquez Cruz, Renato Fernando (2020)
The study area is located northeast of the city of Quito, Pichincha province, Ecuador. Made up of neighborhoods; El Inca II, El Batán, El Inca I, Gabriela Marina, San José del Inca, El Batan Bajo and May 24. The delimitation of the study area has been carried out taking into account the urban morphology (layout), to the north by De Las Bugambillas street, to the south by Hugo Moncayo street, to the east by Eloy Alfaro avenue and to the west by Paris street. The approach of a retail market responds to the fact that through this space the economy of a sector is reactivated and maintained and at the same time, elements such as supply and demand are prioritized. Its main function is to host mainly commercial and direct transactions between the merchant and the consumer, mainly of food products, being a primary production site for the inhabitants of different sectors of the city. The titling project is located between Av. Eloy Alfaro and Av. De los Granados in addition to calle de los Naranjos, it seeks to enhance this location to strengthen the dynamics and activities existing in the sector through the implementation of a market retailer that responds to the needs of the site and users. The project seeks to be a space for interaction between users who come to purchase food products, in addition to giving ownership of the public space to the pedestrian and that in this way it is the consumer himself who conforms the project, integrating it with the different sales spaces, in addition to potentiating and reactivating commerce within traditional markets, which over time has been lost due to the appearance of large supermarket chains.